Exploring the Interplay between Writing Practices and Identity Formation in Academic Contexts - Rahman, Muhammad Arinal; Handrianto, Ciptro; Kenedi, Ary Kiswanto; Ilhami, Aldeva; Ghafar, Zanyar Nathir (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
In academic settings, the relationship between writing practices and identity formation is a cornerstone of scholarly inquiry. As individuals engage in writing, they convey information and construct and negotiate their identities within disciplinary, cultural, and linguistic frameworks. This review paper provides a comprehensive synthesis of existing scholarship on the intricate relationship between writing practices and identity formation in academic contexts. Drawing upon a systematic analysis of 30 studies, the paper illuminates the complex interplay between language, culture, and academic discourse in shaping authorial identities. Key themes explored include conceptualizing writing as an act of identity construction, the challenges faced by distinct student populations in establishing authorial voices, disciplinary variations in identity formation, and pedagogical implications for academic writing instruction. The review integrates diverse theoretical frameworks, such as sociocultural perspectives, academic literacy approaches, and integrationist models, offering a nuanced understanding of the mechanisms underlying identity construction through writing. Furthermore, this review also identifies gaps and potential avenues for future research, including the need for longitudinal studies, the exploration of individual agency in identity formation, and the examination of emerging technologies and interdisciplinary collaborations. Ultimately, this synthesis adds to ongoing conversations about how writing practices affect identity formation. It does this by informing teaching methods and institutional policies that support positive identity development among diverse academic communities.